SEJARAH DAKWAH DATO KARAMA: MENELUSURI ULAMA SUMATERA BARAT PENYEBAR ISLAM DI LEMBAH PALU - Nurdin, Nurdin; Maddini, Harsul (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 14 No 2 (2018)DO - 10.24239/al-mishbah.Vol14.Iss2.119, 2019)
Dato Karama or Abdullah Raqie is an Ulama from Minangkabau West Sumatra who brought Islam to Central Sulawesi. His origin and roles have long been in a debate due to lack of documented resources. Previous studies mostly focus on the arrival of Dato Karama in Palu around 1645 M and the roles he played in spreading Islam after the period. However, none of the scholars have studied the relationship of Dato Karama and his home town in Koto Tangah, Minangkabau, West Sumatra. Through historiography method, we studied the origin of Dato Karama in West Sumatra, his arrival story, and his roles in spreading Islam in Palu Central Sulawesi. We found that Dato Karama lives in a similar period with a well-known Ulama in Koto Tangah Syekh Burhanuddin. We suspect that both of them studied Islam from Syekh Abdul Rauf Singkil Aceh. Dato Karama moved to Central Sulawesi after transit in South Sulawesi together with other three Koto Tangah well-known Ulama; Dato Ribandang, Dato Patimang, and Dato Ri Tiro. The number of artifacts which resemble West Sumatra artifacts can be found in Central Sulawesi. Those evident prove that Dato Karama is an Ulama from West Sumatera.